Law of strata pressure behavior of surrounding rock in nearby goaf roadway for extra-thick coal seams of Datong mine area - Lian, Xiaoyong; Li, Chen; Li, Jun; Wu, Liang (Frontiers in Earth Science, 2023)
In order to solve the problem that the strata pressure behavior of nearby goaf roadway in extra-thick coal seam in Datong mining area was intense, which was affected by the side working face mining. The law of strata pressure behavior of surrounding rock in nearby goaf roadway was studied in detail by various methods, such as laboratory test, theoretical analysis, numerical simulation, and field monitoring. Based on the mine pressure characteristics of nearby goaf roadway, such as roof cracking, two-side deformation, and floor heave, the mechanical test of surrounding rock and the theoretical failure analysis of surrounding rock in mining-induced non-uniform stress field were carried out. The circular-oval-butterfly failure trend of surrounding rock in nearby goaf roadway was obtained under the influence of mining. The steady failure evolution lateral pressure coefficient (λ=0.5~1.8) and butterfly mutation lateral pressure coefficient (λ<0.35 or λ>2.1) of the surrounding rock in nearby goaf roadway of Tongxin coal mine were analyzed. The stress field and plastic zone shape-size characteristics of surrounding rock were analyzed by numerical simulation during excavation and mining (with or without top extraction roadway) of nearby goaf roadway and the theoretical law of mine pressure was obtained in Tongxin Coal mine. Finally, through the field monitoring, the mine pressure behavior of nearby goaf roadway shows the spatial difference, that is, the difference between the stress of two sides and roof and the stress characteristics of deep and shallow in surrounding rock. Grasping the law of mine pressure behavior in nearby goaf roadway would have great practical significance to take targeted measures for controlling surrounding rock stability.